Manajemen Sumber Daya Manusia Strategik: Solusi Untuk Mengoptimalkan Produktivitas, Efisiensi, dan Kinerja Perusahaan di Era Modern - Ni Komang Widyantari; Dewa Putu Yudi Pardita; Ni Made Santini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the implementation of human resource management (HRM) strategies in supporting organizational performance sustainability in the modern era, as well as the role of employee job satisfaction as a mediator between HRM strategies and organizational performance sustainability. The method used in this research is a literature review, referring to various sources and previous studies on HRM and organizational performance. Based on the findings, effective HRM strategies can improve organizational performance by ensuring optimal utilization of employee potential, including through appropriate training and development programs. Employee job satisfaction plays a significant role as a mediator between HRM strategies and organizational performance sustainability, as satisfied employees are more productive and committed to organizational goals. This study concludes that companies need to pay special attention to HRM policies that enhance job satisfaction and continue to innovate in the face of rapidly changing business environments.